Integration of Religious Moderation Values in Fiqh Learning - Ghifari, Fahmul Hikam Al; Alias, Muhamad Firdaus Bin; Sobri, Sobri; Imamuddin, M.; Rahman, Ikhwan (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2025)
The background of this study is rooted in the need to present Fiqh learning that is not only oriented toward normative legal aspects but also instills values of balance, justice, and tolerance in line with the vision of religious moderation promoted by the Ministry of Religious Affairs of the Republic of Indonesia. This study aims to analyze the integration of religious moderation values in Fiqh learning at Madrasah Ibtidaiyah (MI) as a strategy to strengthen inclusive and contextual Islamic education. The method employed is library research, analyzing primary sources such as classical Fiqh texts and scholars’ works on wasathiyah, as well as secondary literature including books, scholarly articles, and government policies related to religious moderation. The findings indicate that the integration of moderation values in Fiqh learning can be implemented through three main channels: curriculum, interactive learning methods, and religious practices in schools. This integration has a positive impact on students’ cognitive, affective, and psychomotor domains, shaping Muslim individuals who are both religious and moderate. The implications of this study emphasize the crucial role of teachers as role models of moderative attitudes and the need for strengthening Fiqh curricula based on moderation to prevent the emergence of intolerance at the elementary level. Thus, Fiqh learning in Madrasah Ibtidaiyah holds great potential to serve as a laboratory of religious moderation that is relevant to the needs of a multicultural nation.